A experiência de uma morte parental em famílias com crianças - Rigão, Gabriela Sarturi (2022)
From a systemic perspective, the present study aimed to understand the experience of families with children who experienced a parental death. In a special way, it sought to know the experience of family grief after the death of parents of children and to understand, from the family narrative, the child's construction of meanings for death and for deceased parents. A qualitative research was carried out, with a descriptive-exploratory character and a collective case study design. Three families with children aged 7 to 10 years old who had lost their father or mother participated in the study. The instruments used with the adults responsible for the family were the Narrative Interview, the Genogram Interview and an Interview on Parental Death in Families with Children, applied in a semi-structured way. The interview with the children was carried out using the “Desenho da Família com Estória” (DF-E) (Drawing of the Family with Story) technique. The resulting data were submitted to Content Analysis. The main results found gave rise to two articles, named: “The experience of families with children who have experienced a parental death” and “Narratives about death: A look to the child and the family after a parental death”. The results underscore the importance of reconstructing roles and functions to follow the family routine and include the deceased caregiver in the child's narrative and family history. Families showed different perceptions about the presence of a continuous bond with the deceased mother or father and the meanings of this death in their families. The sharing of grief and the construction of meanings were crossed by conflicts that current caregivers had with the deceased and by doubts about what should be shared with the child or preserved from him. Still, the adults sought professional support for the management of bereaved children, demonstrating care for the child as paramount and their own sufferings as secondary. In general, the meanings attributed by children to the death of their father or mother corresponded to the way in which their families did it, however, some discrepancies between the narratives of adults and children were highlighted. The children did not seem to perceive the same space for dialogue that the adults mentioned, keeping to themselves some feelings and doubts about the deceased parents. Finally, it was noted the need for children to be heard about their understandings and doubts, with space for the constant recreation of meanings about this challenging period for themselves and for the family system. It is considered relevant to expand knowledge about the experience of families with children who have had significant losses, as well as to provide more spaces for discussion that allow for the elaboration of narratives and constructions of meanings about death and life.